Hydrogen Sulfate-Templated Synthesis of a Bis-Ferrocene Macrocycle - Beeren, Sophie R. (Synlett, 2023)
A bis-ferrocene macrocycle was synthesized by reversible acylhydrazone formation under thermodynamic control, starting from a ferrocene functionalized with hydrazide and protected aldehyde moieties. A hydrogen sulfate anion acts as a template to direct the synthesis specifically toward the macrocyclic dimer, due to a weak but selective binding interaction. This work highlights the utility of dynamic combinatorial chemistry as an approach to macrocycle synthesis.
Keywords: supramolecular chemistry; hydrazones; macrocycles; host–guest systems; ferrocene; dynamic combinatorial chemistry